THE RELATIONSHIP OF THE METHOD OF FAMILY UPBRINGING WITH THE ACADEMIC ASSIMILATION OF STUDENTS (ON THE EXAMPLE OF A SMALL SCHOOL AGE) (Proceedings of International Educators Conference, 2024)
Psychological support beyond the family circle is usually accompanied by strengthening the educational role of communication with peers and adults, media and culture. Thus, training goes to the background, and the main psychological activity of a teenager is aimed at the formation of personality. The school is a transitional period for a teenager to move away from the family and go out into the world independently. On the one hand, it reminds some kind of family: at school, the attitude towards adolescents in childhood is maintained, adults are in the position of a caregiver and make the appropriate requirements.